»FOLGE DEINEM EIGENEN STERN!« - ZUR PRODUKTWERBUNG IM SPIEGEL DER RUSSISCHEN GESELLSCHAFT - Donninghaus, Sabine (Acta Neophilologica, 2007)
The language of product advertising reflects political, social, and economic contexts. Thus, a broad basis of material enables linguists to observe in what way the change of a society becomes visible by strategies of marketing a product or a brand name. In the article, by the example of the legendary and prestigious Mercedes-Benz brand this in shown by way of a semantic-pragmatic analysis. For this it is briefly outlined the career of Mercedes-Benz and today’s socioeconomic situation in Russia. By way of examples from a corpus of Russian advertising copies on this brand, which has been on the Russian market for more than a century, it is then demonstrated how the language of economic advertisement works today and which strategies are used to advertise the various products of the different price ranges. From a gender-linguistic perspective it is sketched the use of rhetorical devices by help of which there is breaking through the conventional expectations of those being in the focus of advertising. It is shown in which way the language of advertisement exploits social cliches to sell a certain image of man, and in which way the unique selling proposition is used to make the product-specific, emotional, and the factually not justifiable additional advantage of the advertised vehicles explicit, which makes them different from their competitors. After having determined the linguistic concept of vagueness I explain the highly unclear nature of the language of advertisement, how this way it fulfills its persuasive function, and how it thus tempts consumers to buy a product which was formerly beyond everybody’s means.